2008
DOI: 10.1016/j.ajhg.2007.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Population Genomics Supports a Single Pre-Clovis Origin with a Coastal Route for the Peopling of the Americas

Abstract: It is well accepted that the Americas were the last continents reached by modern humans, most likely through Beringia. However, the precise time and mode of the colonization of the New World remain hotly disputed issues. Native American populations exhibit almost exclusively five mitochondrial DNA (mtDNA) haplogroups (A-D and X). Haplogroups A-D are also frequent in Asia, suggesting a northeastern Asian origin of these lineages. However, the differential pattern of distribution and frequency of haplogroup X le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
291
3
20

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(346 citation statements)
references
References 63 publications
(101 reference statements)
28
291
3
20
Order By: Relevance
“…One of these (Fagundes et al 2008), claims to refute the SH on the basis of theoretical modelling of a single entry because, on their estimates, American X has a similar age and diversity to the other American mtDNA founders. They argue it could have gone through a similar LGM bottleneck to the other lineages in Beringia and thus claim their… "…results strongly support the hypothesis that haplogroup X, together with the other four main mtDNA haplogroups, was part of the gene pool of a single Native American founding population; therefore they do not support models that propose haplogroup-independent migrations, such as the migration from Europe posed by the Solutrean hypothesis.…”
Section: Arguments Made For X2a Arriving Via Beringiamentioning
confidence: 99%
“…One of these (Fagundes et al 2008), claims to refute the SH on the basis of theoretical modelling of a single entry because, on their estimates, American X has a similar age and diversity to the other American mtDNA founders. They argue it could have gone through a similar LGM bottleneck to the other lineages in Beringia and thus claim their… "…results strongly support the hypothesis that haplogroup X, together with the other four main mtDNA haplogroups, was part of the gene pool of a single Native American founding population; therefore they do not support models that propose haplogroup-independent migrations, such as the migration from Europe posed by the Solutrean hypothesis.…”
Section: Arguments Made For X2a Arriving Via Beringiamentioning
confidence: 99%
“…For instance, although when and how early modern humans reached America for the first time was subject to debates (eg, Waters and Stafford 16 and Goebel et al 17 ), demographic inferences using mitochondrial DNA (mtDNA) sequences indicated an initial differentiation from Asian populations ended with a moderate bottleneck in Beringia during the last glacial maximum (LGM), around 23 000 to 19 000 years ago. 18 Then, toward the end of the LGM, a strong spatial and demographic population expansion started 18 000 and finished 15 000 years ago (thus well before the Neolithic transition).…”
Section: Introductionmentioning
confidence: 99%
“…7 The last inhabitants of former Beringia, reflected genetically in the Yukaghir, Chukchi, Eskimo-Aleuts, Na-Dene, and Northwestern North American Indians, have been a focus of extensive comparisons between complete mtDNA sequences from Siberia and from North America. As a result, the Siberian affinities of major Native American mtDNA haploclusters (A-D), initially detected by comparing a few single-nucleotide polymorphisms of similar haplotypes from Eurasia and the Americas, [7][8][9][10][11][12][13][14] have been revised and extended. It has become evident that the range of distinct lineages confined to the entire Eskimo Arctic is a subset of haplogroups A2a, A2b, D2a, and D4b1a2a1, though each of their evolutionary histories is far from being explicitly clear.…”
Section: Introductionmentioning
confidence: 99%